EXCESSIVE CREDIT GROWTH OR CATCHING UP PROCESS: THE CASE OF CENTRAL, EASTERN AND SOUTHEASTERN EUROPEAN COUNTRIES - Stojanović, Dušan; Stojanović, Danilo (Economic Annals, 2015)
Most CESEE countries had an impressive credit growth prior to the outbreak of the financial crisis in 2008. Nevertheless, that experience has taught us that the strong expansion of private sector credit must not be ignored. In an attempt to investigate whether the rapid credit growth was a result of the catching-up process or was a risky process with well-known consequences, we performed empirical analysis by applying statistical (HP filter) and econometric (pooled OLS, fixed effect OLS, and PMG) approaches. The empirical results of both out-of-sample and in-sample approaches suggest that in the pre-crisis period excessive credit growth in terms of higher actual than estimated credit growth was recorded for the majority of the countries observed. Compared to the outof-sample approach, in-sample estimates, which turned out to be more reliable, indicate that the pre-crisis growth was less pronounced and that over the post-crisis period actual credit growth fluctuated around the estimated growth, pointing to the fact that the former was in line with movements in its fitted values.